Direct probing Se spatial distribution in Cu(InxGa1−x)Se2 solar cells: A key factor to achieve high efficiency performance. (January 2016) - Lin, Tzu-Ying; Chen, Chia-Hsiang; Huang, Wei-Chih; Ho, Wei-Hao; Wu, Yan-Huie; Lai, Chih-Huang
Abstract: Control of Se content during manufacturing process has been known to determine the efficiency of Cu(In x Ga1− x )Se2 (CIGS) solar cells. However, how Se is distributed in CIGS films and how Se distribution in hundred-nanometer scale affects the cell performance have not been realized due to limited spatial resolution of composition mapping technique. In this study, a promising nondestructive analysis by using field-emission electron probe microanalysis (FE-EPMA) is first demonstrated to directly probe the Se distribution within the depletion region of CIGS absorbers. We observe that Se-deficient-related defects are still exist in CIGS films even with high Se concentration but non-uniform distribution, leading to relatively low efficiency (~7%). By correlating photoluminescence spectra and conductivity mapping with composition distribution, we clarify that the uniform Se distribution is the key factor to suppress the defect formation and to enhance the p–n inversion at grain boundaries, resulting in significant efficiency boost to 12%. Graphical abstract: Highlights: We demonstrate a promising composition mapping, FE-EPMA. The Se distribution within the depletion region of CIGS absorber is investigated. The Se distribution is correlated with defect formation and grain boundary property. Uniform Se distribution suppresses the defect formation, resulting in efficiency boost of 70%.